2015
DOI: 10.1002/eji.201445284
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic switch of CD8+ T cells reactivated under hypoxia toward IL‐10 secreting, poorly proliferative effector cells

Abstract: CD8+ T cells controlling pathogens or tumors must function at sites where oxygen tension is frequently low, and never as high as under atmospheric culture conditions. However, T-cell function in vivo is generally analyzed indirectly, or is extrapolated from in vitro studies under nonphysiologic oxygen tensions. In this study, we delineate the role of physiologic and pathologic oxygen tension in vitro during reactivation and differentiation of tumor-specific CD8 + T cells. Using CD8 + T cells from pmel-1 mice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 80 publications
(98 reference statements)
11
50
1
Order By: Relevance
“…5% and 1% O 2 . It is noteworthy that 21% O 2 is the commonly used percentage of oxygen for cell culture, but it corresponds to the atmospheric environment rather than any physiologic conditions [44]. Moreover, we observed that GIC susceptibility to FASL-mediated cell death was higher than for GDCs (Fig 3A), and one can speculate that this result is in accordance with the higher level of FAS surface expression by GICs.…”
Section: Discussionsupporting
confidence: 64%
“…5% and 1% O 2 . It is noteworthy that 21% O 2 is the commonly used percentage of oxygen for cell culture, but it corresponds to the atmospheric environment rather than any physiologic conditions [44]. Moreover, we observed that GIC susceptibility to FASL-mediated cell death was higher than for GDCs (Fig 3A), and one can speculate that this result is in accordance with the higher level of FAS surface expression by GICs.…”
Section: Discussionsupporting
confidence: 64%
“…5). Recent studies suggested that the enhanced expression of IL-10 during hypoxia directly inhibits T H 1 priming [31-33], and that STAT3 activation under hypoxia decreases T H 1 activation [27, 34]. However, further investigations are required to identify the exact mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that T cell priming under low O 2 fractions can increase differentiation of CD8 + T cells toward more lytic effector cells, even if these may be fewer in number because of reduced expansion 21,28,42,48 . Specifically, granzyme A and B were upregulated when CTLs were generated under physiological normoxia, as were FasL and Blimp-1, with capacity to secrete higher amounts of IFNγ 21,49 .…”
Section: Low Oxygen Fractions and T-cell Primingmentioning
confidence: 99%
“…Specifically, granzyme A and B were upregulated when CTLs were generated under physiological normoxia, as were FasL and Blimp-1, with capacity to secrete higher amounts of IFNγ 21,49 . The metabolic profile of the cells was also described to switch from an oxidative phosphorylation metabolism toward a more glycolytic one when O 2 availability was lowered 38 .…”
Section: Low Oxygen Fractions and T-cell Primingmentioning
confidence: 99%